Varón de 66 años con diabetes mellitus tipo 2 y obesidad - Delgado Amaiquema, Jaccely Leonor (2018)
Diabetes mellitus type II is a pathology that seriously affects Ecuador, being the third cause of death in the country, an indicator that should promote the population to carry a better food quality and avoid suffering from this disease. The patient to be treated is an adult over 66 years of age who weighs 179 kg and a height of 1.53 meters. The patient was diagnosed with Type 2 Diabetes Mellitus 5 years ago. He goes to the consultation with his Endocrinologist because lately he has felt bad, presents signs and symptoms such as sudden dizziness and nausea despite taking daily his medicine for diabetes which is sitagliptin and metformin 50mg / 850mg 1 daily, in terms of relevant biochemical tests Its glycosylated hemoglobin values are outside the normal parameters, which reveals that the patient has uncontrolled diabetes. The patient needs to apply nutritional therapy in order to solve his problem, which will be adequate for the needs of the individual and control of the pathology; with the purpose of avoiding the worsening and suffering of possible complications such as nephropathy, retinopathy, among others.